The Effect of Realistic Mathematics Educations (RME) Approach Based on Ethnomatics on the Improvement of Concept Understanding Ability and Students' Learning Motivation in Elementary School Al-Kausar City of Langsa - Nuraina Nuraina; KMS. M. Amin Fauzi; Naeklan Simbolon (BIRCU, 2021)
This study aims to determine: (1) The effect of the ethnomatematics-based RME approach on improving the understanding of the fourth grade students' mathematical conceptual understanding of Al-Kausar Elementary School Langsa City, (2) The effect of the ethnomatematics-based RME approach on increasing the learning motivation of fourth grade students of SD Al-Kausar Kota Langsa, (3) There is an interaction between the learning approach and the initial mathematical ability to increase the students' understanding of mathematical concepts in grade IV SD Al-Kausar, Langsa City, (4) There is an interaction between the learning approach and learning motivation towards the increase in the ability to understand the mathematical concepts of fourth grade students Al-Kausar Kota Langsa, and (5) Describing students' ability to understand mathematical concepts in terms of high, medium and low abilities. The sample in this study was selected by total sampling of two classes. The first class (first group) was treated by applying the RME approach based on ethnomatics with a sample size of 25 students and the second class (second group) was treated with conventional learning with a sample size of 25 students. The data in this study were analyzed using 2-way ANOVA. From the research results, it is obtained that there is an effect of the ethnomatematic based RME approach on the improvement of students 'understanding of mathematical concepts, where as much as 47% of the ethnomatematic based RME approach affects the increase in students' understanding of mathematical concepts.This study aims to determine: (1) The effect of the ethnomatematics-based RME approach on improving the understanding of the fourth grade students' mathematical conceptual understanding of Al-Kausar Elementary School Langsa City, (2) The effect of the ethnomatematics-based RME approach on increasing the learning motivation of fourth grade students of SD Al-Kausar Kota Langsa, (3) There is an interaction between the learning approach and the initial mathematical ability to increase the students' understanding of mathematical concepts in grade IV SD Al-Kausar, Langsa City, (4) There is an interaction between the learning approach and learning motivation towards the increase in the ability to understand the mathematical concepts of fourth grade students Al-Kausar Kota Langsa, and (5) Describing students' ability to understand mathematical concepts in terms of high, medium and low abilities. The sample in this study was selected by total sampling of two classes. The first class (first group) was treated by applying the RME approach based on ethnomatics with a sample size of 25 students and the second class (second group) was treated with conventional learning with a sample size of 25 students. The data in this study were analyzed using 2-way ANOVA. From the research results, it is obtained that there is an effect of the ethnomatematic based RME approach on the improvement of students 'understanding of mathematical concepts, where as much as 47% of the ethnomatematic based RME approach affects the increase in students' understanding of mathematical concepts.